ELDERLY WITH ABSOLUTE INSULIN DEFICIENCY IN A SENIOR CARE FACILITY: A TAILORED APPROACH - Evali, Suprhamanyam; Dorefl, Davyina Divasyini; Rahim, Anilah Abdul; Rahmatullah, Ijaz Hallaj (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Managing diabetes in elderly insulin-deficient patients poses significant challenges, particularly when social support is limited. CASE We present an elderly female with recurrent diabetic ketoacidosis (DKA) and frequent hypoglycemic episodes. Despite various insulin regimens, she experienced unpredictable glycemic fluctuations, complicated by hypo- glycemia unawareness. A 65-year-old frail Chinese female with poor social support and underlying medical conditions such as diabetes mellitus (DM), hypertension and dyslipidemia, was first admitted due to loss of consciousness at home. She was diagnosed with DKA secondary to pneumonia. After stabilization, she was transferred back to a district hospital. Despite trials of multiple insulin regimens -basal-bolus, basal insulin plus sulfonylurea and premixed insulin, she continued to experience multiple episodes of hyperglycemia and hypo- glycemia. Laboratory findings showed a low/undetectable C-peptide level, confirming insulin deficiency. After discussion with endocrinologists, she was transitioned to a basal-bolus regimen with s/c Toujeo 10 u OM and s/c Novorapid 6 u tds, leading to improved glycemic control but still unpredictable glycemic readings. Given her planned placement in a nursing home, carbohydrate counting was impractical. Instead, we collaborated with a dietitian and elderly home nursing staff to implement a structured meal-based insulin dosing strategy based on her total daily insulin requirement (0.4 units/kg/day), insulin sensitivity ratio (1 unit: 3 mmol/l), and insulin-to-carbohydrate ratio (1 unit per 14g CHO). This approach significantly stabilized her blood sugar, preventing further hypoglycemia and DKA episodes. CONCLUSION This case underscores the complexity of insulin manage- ment in elderly patients with insulin deficiency. Rather than carbohydrate counting, a structured meal-based insulin regimen proved to be a viable solution in a nursing home setting, ensuring safe and effective glycemic control.